PERANAN SENYAWA FENOLIK DALAM MENURUNKAN GLUKOSA DARAH PADA PENDERITA DIABETES MELITUS TIPE 2 - Made Gendis Putri Pertiwi; Firman Fajar Perdhana (Faculty of Agriculture Science & Technology, 2023)
Diabetes mellitus (DM) is a metabolic disorder commonly in developing countries. The number of DM patient increases anual. Oxidative stress conditions is trigger that cause of DM. An imbalance in the amount of Reactive Oxygen Species (ROS) with antioxidants in the body encourages damage to pancreatic beta-cells that can result in decreased insulin secretion. Beside DM treatment is done by injecting insulin or synthetic oral drugs, consumption foods that is rich phenolic compounds can be an alternative in lowering blood glucose. Phenolic compounds are able to act as antioxidant agents that prevent and inhibit the formation of free radicals from lipid peroxidation processes so that they can suppress oxidative stress in the pancreas. Phenolic compounds also have the potential to act as inhibitors of alfa-amylase and alfa-glucosidase enzymes which can delay the digestion of carbohydrates so that glucose absorption decreases. Inhibiting this enzyme is one way to keep glucose level normal especially after eating. Therefore, consumption foods high in phenolic compounds can reduce the risk of developing degenerative diseases, especially diabetes.